Enantioselective synthesis of (+)-Sedridine, (-)-Allosedridine and their N-Methyl analogs via Maruoka-Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Suryavanshi, Gurunath (Natural Product Research, 2023)
A simple synthetic approach has been developed for the enantioselective total synthesis of (+)-Sedridine, (-)-Allosedridine and their analogs such as (+)-N- Methyl Sedridine and (-)-N-Methylallosedridine. The synthesis was achieved by using commercially available starting materials via Maruoka-Keck allylation, Wacker oxidation, and CBS reduction. The synthetic root provides a good diastereomeric ratio and high yields.
Keywords: CBS reduction; Maruoka-Keck allylation; Piperidine; Wacker oxidation